Presence, function, and regulation of IL‐17F‐expressing human CD4+ T cells. Issue 4 (16th January 2020) - Burns, Lachrissa A.; Maroof, Ash; Marshall, Diane; Steel, Kathryn J. A.; Lalnunhlimi, Sylvine; Cole, Suzanne; Catrina, Anca; Kirkham, Bruce; Taams, Leonie S.
Abstract: The pro‐inflammatory cytokine IL‐17A has been implicated in the immunopathology of inflammatory arthritis. IL‐17F bears 50% homology to IL‐17A and has recently been suggested to play a role in inflammation. We investigated the induction and cytokine profile of IL‐17F + CD4 + T cells, and how IL‐17F may contribute to inflammation. Upon culture of healthy donor CD4 + T cells with IL‐1β, IL‐23, anti‐CD3, and anti‐CD28 mAb, both IL‐17A and IL‐17F‐expressing cells were detected. In comparison to IL‐17A + IL‐17F − CD4 + T cells, IL‐17F + IL‐17A − and IL‐17A + IL‐17F + CD4 + T cells contained lower proportions of IL‐10‐expressing and GM‐CSF‐expressing cells and higher proportions of IFN‐γ‐expressing cells. Titration of anti‐CD28 mAb revealed that strong co‐stimulation increased IL‐17F + IL‐17A − and IL‐17A + IL‐17F + CD4 + T cell frequencies, whereas IL‐17A + IL‐17F − CD4 + T cell frequencies decreased. This was partly mediated via an IL‐2‐dependent mechanism. Addition of IL‐17A, IL‐17F, and TNF‐α to synovial fibroblasts from patients with inflammatory arthritis resulted in significant production of IL‐6 and IL‐8, which was reduced to a larger extent by combined blockade of IL‐17A and IL‐17F than blockade of IL‐17A alone. Our data indicate that IL‐17A and IL‐17F are differentially regulated upon T cell co‐stimulation, and that dual blockade of IL‐17A and IL‐17F reduces inflammation more effectively than IL‐17A blockade alone. Abstract : High‐strength T cell stimulation enhances the frequency of IL‐17F + CD4 + T cells in part via an IL‐2 dependent manner. Results demonstrate IL‐17A + and IL‐17F + CD4 + T cell populations display different cytokine profiles. Combined blockade of IL‐17A and IL‐17F is more effective at reducing inflammation than blockade of IL‐17A alone.